A Review of the Properties of Electro Less Duplex Coatings with Different Outer Layers and Bath Preparations - Sandip Ghosh; Arka Bhattarcharee; Subhadip Maity; Amrita Pradhan; Sourav Dey (International Journal of Electro-Mechanics and Material Behaviour, 2023)
Electroless coatings are widely used now because of their outstanding tribological as well as physical qualities. The need for a coating or finished product with any of these attributes has increased over the past few years. As a consequence, there has been a rise in the amount of study and associated publishing production on the creation of various surface types and coverings with various components. This study gave rise to the notion of on-linear" coverings. Several sorts of layers are generated in such coverings that overlay over one another to give qualities that are superior to the layer thickness. The study provides an overview of the levels implemented in numerous duplex coatings, their electroplating solutions following recommendations, as well as how the resulting multi-layers impact their final qualities.
Keywords: Alloys; Corrosion; Duplexes; Electroless Coating; Ni-P coating; Properties